2020
DOI: 10.1111/ecc.13321
|View full text |Cite
|
Sign up to set email alerts
|

The perceived effect of parental cancer on children still living at home: According to oncology health professionals

Abstract: In Australia, the projected estimate for new cancer cases among adults aged 25-49 years is 16,715, accounting for 8.66% of all new cancer cases in 2019 (AIHW, 2019). Reported 5-year survival rates suggest patients and their families are living longer with the impact of a cancer diagnosis (Werner-Lin & Biank, 2009). This younger cohort is likely to be in the workplace or studying, and many will have dependent children living at home (Semple & McCaughan, 2013; Werner-Lin & Biank, 2009). In Australia, there are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(28 citation statements)
references
References 38 publications
0
25
0
3
Order By: Relevance
“…Thus, while professionals empathised with the parents, recognising that they might be having difficulties accepting their prognosis and have the desire to protect their own children from distress, their own perceived duty to the child led to a dilemma that left them feeling powerless [ 18 , 19 , 21 , 22 , 25 – 27 ]: “Some nurses found it difficult when parents were persistent in their determination to protect their children from matters related to their illness and forthcoming death, and in these cases relied on the parents to take responsibility for their children…. Nurses indicated that they knew that by law, children have the right to professional advice, support and information, but at the same time the nurses knew they could not defy the wishes of the parents.” [ 26 ] …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, while professionals empathised with the parents, recognising that they might be having difficulties accepting their prognosis and have the desire to protect their own children from distress, their own perceived duty to the child led to a dilemma that left them feeling powerless [ 18 , 19 , 21 , 22 , 25 – 27 ]: “Some nurses found it difficult when parents were persistent in their determination to protect their children from matters related to their illness and forthcoming death, and in these cases relied on the parents to take responsibility for their children…. Nurses indicated that they knew that by law, children have the right to professional advice, support and information, but at the same time the nurses knew they could not defy the wishes of the parents.” [ 26 ] …”
Section: Resultsmentioning
confidence: 99%
“…While still emotionally difficult for professionals in general, these were instances where their psychological burden was reduced [ 23 ]. Professionals had a harder time if they had less experience with children, either professional [ 19 , 24 , 27 ] or personal [ 27 , 31 ], to draw on.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations